Avaliação do uso da polaridade negativa na soldagem de passes de enchimento pelo processo MIG/MAG duplo arame - Mishchenko, Andrii (2014)
It is expected from filling passes to present proper penetration, fusion on the grove-sides and enough deposition rate to fill up the joint with the fewest number of passes as possible. One of the methods from which is expected high efficiency on this aspect is the MIG/MAG Double Wire, which combines the versatility and practicality of the conventional MIG/MAG with an increased productivity. Another means of augmenting the MIG/MAG production capacity is the use of negative polarity. In spite of being a simple approach, its limitations refrain the process from practical applications. However, one can foresee a possibility to increase the MIG/MAG Double Wire production capacity through the use of negative polarity. Thus, the general objective of this work was to assess the combination of positive polarity in the leading wire with negative polarity in the trailing wire on the performance of the process when applied to filling passes. The assessment of this approach performance was carried out through a comparative study between the conventional combination (two wires working in pulsed mode with positive polarity) and combinations with positive polarity at the leading wire but negative polarity in the trailing wire (pulsed negative polarity or controlled shortcircuit negative polarity). For comparative purposes, the average current of each wire and the amount of metal deposited per joint unit length were kept constant. The influence of the negative polarity in the trailing wire on the bead geometry, bead surface finish and process capacity was pursuit. The evaluation was made under different conditions of filling pass deposition, such as flat position single pass, lap joint of thin sheets, flat position multi-pass welding and an overhead position single pass. The results showed the viability of the MIG/MAG Double Wire with negative polarity in the trailing wire for filling passes welding in the flat position, once this approach allowed completing the same joint configuration faster and imputing less heat. However, the technique using negative polarity showed restriction when applied in the overhead position.